2019
DOI: 10.1001/jamadermatol.2019.1783
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Ustekinumab Levels With Clinical Response in Psoriasis

Abstract: ; for the British Association of Dermatologists Biologic and Immunomodulators Register (BADBIR) Study Group and the Psoriasis Stratification to Optimise Relevant Therapy (PSORT) Consortium IMPORTANCE High-cost biologic therapies have transformed the management of immune-mediated inflammatory diseases. To optimize outcomes and reduce costs, dose adjustment informed by measurement of circulating drug levels has been shown to be effective in various settings. However, limited evidence exists for this approach wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…and Zhou et al ., we maximized clinical relevance by including covariates already known to affect response to biologics across the BADBIR cohort. As reported elsewhere, we also confirm in our real‐world cohort that ustekinumab has relatively low immunogenicity in the setting of clinical practice, with only 3.3% of patients developing detectable ADA …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…and Zhou et al ., we maximized clinical relevance by including covariates already known to affect response to biologics across the BADBIR cohort. As reported elsewhere, we also confirm in our real‐world cohort that ustekinumab has relatively low immunogenicity in the setting of clinical practice, with only 3.3% of patients developing detectable ADA …”
Section: Discussionsupporting
confidence: 90%
“…As reported elsewhere, we also confirm in our real-world cohort that ustekinumab has relatively low immunogenicity in the setting of clinical practice, with only 3.3% of patients developing detectable ADA. 23 Our study had some limitations. As with any real-world cohort, a key issue is missing data.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly to our previous work to develop a model using clinical baseline factors to predict serious infection in patients starting biologic therapies, clinical factors appear to be poorly predictive of drug discontinuation due to ineffectiveness. Work by the Psoriasis Stratification to Optimise Relevant Therapy (PSORT) consortium in the UK has identified that pharmacokinetic factors such as early drug levels are important for prediction of later treatment response for adalimumab and ustekinumab, and it may be that the determinants of biologic pharmacokinetics such as propensity to develop antidrug antibodies or other factors affecting distribution and bioavailability of biologic therapies are more predictive of drug ineffectiveness than are clinical covariates. In addition, there may be other unmeasured factors that might be predictive of biologic ineffectiveness, such as genomic and transcriptomic data, and drug adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Other alternative therapies such as acitretin and methotrexate are less studied but are known to have a slower onset of action. Adalimumab and ustekinumab have also been useful in treating patients with moderate to severe plaque psoriasis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%